The power of geometric algebra computing - Hildenbrand, Dietmar, 1961- (Boca Raton : CRC Press, 2022)
Geometric Algebra is a very powerful mathematical system for an easy and intuitive treatment of geometry, but the community working with it is still very small. The main goal of this book is to close this gap from a computing perspective in presenting the power of Geometric Algebra Computing for engineering applications and quantum computing. The Power of Geometric Algebra Computing is based on GAALOPWeb, a new user-friendly, web-based tool for the generation of optimized code for different programming languages as well as for the visualization of Geometric Algebra algorithms for a wide range of engineering applications. Key Features: Introduces a new web-based optimizer for Geometric Algebra algorithms Supports many programming languages as well as hardware Covers the advantages of high-dimensional algebras Includes geometrically intuitive support of quantum computing This book includes applications from the fields of computer graphics, robotics and quantum computing and will help students, engineers and researchers interested in really computing with Geometric Algebra.
"Chapman & Hall book"
OCLC-licensed vendor bibliographic record.
Keywords: Clifford algebras; Conformal geometry; Quantum computing; Engineering -- Data processing; COMPUTERS / Computer Graphics / General; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Computer Science